The Role of Melanin-Concentrating Hormone and Its Receptors in Energy Homeostasis - MacNeil, Douglas J. (Frontiers in Endocrinology, 2013)
Extensive studies in rodents with melanin-concentrating hormone (MCH) have demonstrated that the neuropeptide hormone is a potent orexigen. Acutely, MCH causes an increase in food intake, while chronically it leads to increased weight gain, primarily as an increase in fat mass. Multiple knockout mice models have confirmed the importance of MCH in modulating energy homeostasis. Animals lacking MCH, MCH-containing neurons, or the MCH receptor all are resistant to diet-induced obesity. These genetic and pharmacologic studies have prompted a large effort to identify potent and selective MCH receptor antagonists, initially as tool compounds to probe pharmacology in models of obesity, with an ultimate goal to identify novel anti-obesity drugs. In animal models, MCH antagonists have consistently shown efficacy in reducing food intake acutely and inhibiting body-weight gain when given chronically. Five compounds have proceeded into clinical testing. Although they were reported as well tolerated, none has advanced to long-term efficacy and safety studies.